Complementary alternative medicine use in children with type 1 diabetes mellitus in Erzurum, Turkey - (:unkn) unknown (WILEY, 2009)
Aim and objective. The aims of this study were: (i) to determine the types of complementary and alternative medicine use among children with type I diabetes mellitus as reported by parents and (ii) to describe sociodemographic and medical factors associated with the use of such treatments in families residing in Eastern Turkey. Background. Type 1 diabetes mellitus is a tremendously challenging and complex disease for children and families to manage. Therefore, the use of complementary and alternative medicines among children with type 1 diabetes is becoming increasingly popular. Design. Survey. Method. Parents of 100 paediatric patients (who were diagnosed with type 1 diabetes at least 6 months prior to the study) who visited the participating paediatric endocrinology multidisciplinary centres and clinics for diabetes management were included in the study. Data were collected by using a semi-structured questionnaire. Results. Fifty-two per cent of the parents reported the use of one or more complementary alternative medicine therapies. Most such users (59 center dot 6%) were using oral herbal preparations; including morus alba (leaves) aloe vera and stinging nettle. Conclusion. Since we found that 78 center dot 6% of those using herbals were satisfied with their results and 69 center dot 2% were planning to continue use, it is important for healthcare providers to have relevant knowledge about complementary alternative medicine use and learn about its efficacy and effects (positive and adverse) of these treatments. Relevance to clinical practice. Botanical substitute for insulin seems unlikely, but complementary alternative treatments may provide valuable clues for the development of new oral hypoglycaemic agents and simple dietary agents. It is important for healthcare providers to have up-to-date knowledge about the use and effects of complementary alternative medicines in the outpatient clinical care setting.
Keywords: children; complementary alternative medicine; nurses; nursing; type 1 diabetes mellitus; TRADITIONAL PLANT MEDICINES; EASTERN TURKEY; THERAPIES; TRENDS; ADULTS; TRIAL; HERBS